Reduction of Sonication-Assisted Graphene Oxide via Chemical and Thermal Treatments - Fattin Diana Junaidi, Nurul; Hidayati Othman, Nur; Nadia Ismail, Ili; Hashimah Alias, Nur; Zaman Shahruddin, Munawar; Hayati Jarni, Husna; Fiqri Zainuddin, Mohammad; Raikhan Nik Him, Nik; Fazlida Hanim Abdullah, Wan (International Journal of Engineering and Technology, 2018)
Graphene has sparked an intense interest in the energy field over the recent years due to its excellent mechanical, electrical, thermal and optical properties. There are several ways to produce graphene, however, large-scale production of this material is still an issue and subjected to intense research effort.Â  In this work, graphene oxide (GO) was first synthesized using sonication-assisted oxidation of graphite followed by reduction process. The reduced graphene oxides (rGOs) are then produced using two routes; chemical L-ascorbic acid (AA) reduction and thermal reduction (T). The sonication process facilitates the washing step and reduces the time required to produce rGOs. The chemical and structural properties of the rGOs were comparatively investigated using XRD, FTIR, BET and FESEM. Results showed that both chemical and thermal methods were effective in removing oxygen-containing functional groups in GO and restore the electrical conductivity of the obtained rGO. rGO-T700 had the highest electrical conductivity (56.39 S/m) in comparison to rGO-T300 (15.87 S/m) and rGO-T500 (35.6 S/m) that were obtained using thermal reduction method. The rGO-AA, which used L-ascorbic acid as a reductant possessed an electrical conductivity of 46.87 S/m. Although this value was slightly lower as compared to rGO-T700, it still demonstrated the potential of using environmentally friendly ascorbic acid for rGO synthesis compared to thermal reduction. The elimination of high temperature reduction could significantly save the production cost and it is believed that further optimization of reduction process parameters might enhance the conductivity of rGO-AA.Â Â